2014
DOI: 10.1055/s-0034-1396422
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Node Biopsy in Pediatric Patients: The Experience in a Single Institution

Abstract: Sentinel lymph node biopsy (SLNB) is an established staging technique in many malignancies, but reports describing this procedure for the evaluation of regional lymph nodes in childhood and adolescents are still scarce. SLNB has progressively gained a role in the staging of pediatric melanoma and some histotypes among soft tissue sarcomas (rhabdomyosarcoma, synovial sarcoma, epithelioid sarcoma, and clear cell sarcoma). We report our experience with 29 patients who were evaluated with SLNB during the past 12 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…Our study confirms previous reports of the feasibility and safety of performing SLNB in pediatric and AYA sarcoma patients . Contemporary cooperative group protocols now require nodal sampling for patients with extremity rhabdomyosarcoma even without clinical or radiographic evidence of nodal metastasis because of the relatively high frequency of regional metastases and the possibility that physical examination and cross‐sectional imaging may underestimate the presence of metastatic disease.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Our study confirms previous reports of the feasibility and safety of performing SLNB in pediatric and AYA sarcoma patients . Contemporary cooperative group protocols now require nodal sampling for patients with extremity rhabdomyosarcoma even without clinical or radiographic evidence of nodal metastasis because of the relatively high frequency of regional metastases and the possibility that physical examination and cross‐sectional imaging may underestimate the presence of metastatic disease.…”
Section: Discussionsupporting
confidence: 88%
“…In the only published pediatric study comparing PET‐CT with SLNB in pediatric sarcoma patients, 3 of 8 patients had hypermetabolic regional nodes; this was consistent with metastases on PET‐CT, but only 1 was found to contain tumor on SLNB . In agreement with that smaller study, we have demonstrated that PET‐CT had a positive predictive value of only 29%, and this suggests that PET‐CT cannot be used exclusively for the identification of metastatic disease in the pediatric population and cannot be a substitute for tissue sampling . This finding cannot be explained by minimal tumor burden alone in the histologically positive nodes because there was no correlation between disease burden per the pathology report and PET‐CT detection.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Sentinel lymph node biopsy is a reliable staging technique and yield positive results. It was positive most commonly associated with alveolar RMS, followed by Ewing sarcoma, myxoid liposarcoma, epitheloid sarcoma and positive in one patient with embryonal RMS out of 29 patients' studied [16].…”
Section: Discussionmentioning
confidence: 90%